1997
DOI: 10.1136/bmj.314.7094.1625
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal blood blisters are known as angina bullosa haemorrhagica

Abstract: Editor-Five years ago, when we published our research on the discrimination faced by ethnic minority doctors applying for posts as senior house officers, 1 the Department of Health considered using our methodology to monitor progress in tackling discrimination. At a recent BMA conference to discuss racial discrimination in the medical profession several speakers pointed out that racial discrimination was still endemic in the NHS and that direct policy initiatives to tackle specific examples of discrimination-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…[ 9 ] Less frequently, the lesions have also been reported in the oropharynx and esophagus. [ 12 ] The lesions are usually asymptomatic however, they may be associated with pain and burning sensations of the mucosa due to ulcerations. Few patients complain of slight discomfort, xerostomia, tingling and tightness, difficulty in swallowing, choking (angina means choking), or gagging reflex if the lesions are large and seen in faucillar pillars, arytenoids, oropharynx, posterior pharynx, epiglottis, or esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Less frequently, the lesions have also been reported in the oropharynx and esophagus. [ 12 ] The lesions are usually asymptomatic however, they may be associated with pain and burning sensations of the mucosa due to ulcerations. Few patients complain of slight discomfort, xerostomia, tingling and tightness, difficulty in swallowing, choking (angina means choking), or gagging reflex if the lesions are large and seen in faucillar pillars, arytenoids, oropharynx, posterior pharynx, epiglottis, or esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Few patients complain of slight discomfort, xerostomia, tingling and tightness, difficulty in swallowing, choking (angina means choking), or gagging reflex if the lesions are large and seen in faucillar pillars, arytenoids, oropharynx, posterior pharynx, epiglottis, or esophagus. [ 12 ] Airway obstruction has also been reported very rarely with palatal or pharyngeal blisters. The patient should be made aware of the complications and advised to report immediately if symptoms persist as bullae have to be ruptured under supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually mention bullae forming during or shortly after a meal. Some patients report burning just before the blister onset, but pain and burning disappear after the bursting of the bullae 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although ABH is accepted as a benign disorder, some authors reported a choking or gagging sensation when the lesions are in the posterior pharynx or in the epiglottis 3 . As a rare complication, acute upper airway obstruction was also reported 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Although ABH is accepted as a benign disorder, some authors reported a choking or gagging sensation when the lesions are in the posterior pharynx or in the epiglottis. [9] As a rare complication, acute upper airway obstruction was also reported. [10] Given the clinical characteristics of this disease, a specific treatment is unnecessary in most cases, recommending a symptomatic treatment of the lesions.…”
Section: Pathophysiologymentioning
confidence: 99%